Implementation of the common agricultural policy in building sustainable business models in rural areas of Bulgaria - Turlakova, Teodorina (Leadership, Society, Strategic Visions, 2021)
The development and maintenance of applicable business models in rural areas requires support at different levels of government. The implementation of the EUâ€™s Common agricultural policy (CAP) measures in the rural areas creates the conditions for increasing the added value achieved through a number of initiatives, including through the concept of â€œsmart villagesâ€. The purpose of this article is to identify successful business models in rural areas of Bulgaria on the basis of an assessment of the local environment and in line with the CAP priorities. The article defi nes the concepts of â€œbusiness modelâ€ and â€œrural entrepreneurshipâ€, an analytical methodology assesses the business environment in several rural areas in Bulgaria.